AN ANALYSIS OF POLITENESS STRATEGIES USED BY TEACHER AND STUDENTS OF X IBB IN SMAN 1 SUKASADA DURING ENGLISH CLASSROOM INTERACTION - Widana, I M; Swandana, I W; Wedhanti, N K (Journal of Psychology and Instructions, 2018)
This study aims to (1) analyzing the types of politeness strategies used by teachers and students of Class X in Ilmu Budaya dan Bahasa (IBB) in Sekolah Menengah Atas Negeri 1 Sukasada during English classroom interaction; (2) analyzing the factors that influence the choice of politeness strategies. This study was designed as a qualitative descriptive study. The data that has been obtained was analyzed based on the theory of politeness Brown and Levinsons strategy. The results of this study indicated that (1) there were three types of Brown and Levinson politeness strategies used by teachers and students namely bald on record, positive politeness, and negative politeness; (2) as for the factors that influencing the choice of politeness strategies are payoffs: as a prior consideration, circumstances: social variables, and integration of the assessment of payoffs and the weight of the risk of choosing politeness strategies.